A thermo-alkali stable and detergent compatible processive β-1,4-glucanase from Himalayan Bacillus sp. PCH94 - Thakur, Vikas; Singh, Dharam (Frontiers in Microbiology, 2022)
Present study reports a novel and robust GH9 processive endoglucanase β-1,4-glucanase from Bacillus sp. PCH94 (EGaseBL) with thermo-alkali stable properties. The EGaseBL gene was cloned in pET-28b(+) and expressed in E. coli BL21(DE3) cells. The recombinant protein was purified 94-fold with a yield of 67.8%. The biochemical characterization revealed an active enzyme at a wide pH (4.0 to 10.0) and temperature (4 to 100 ºC). It showed a Km and Vmax of 1.10 mg/mL and 208.24 IU/mg, respectively, using β-glucan as a substrate. The EGaseBL showed dual activities for endoglucanase (134.17 IU/mg) and exoglucanase (28.76 IU/mg), assayed using substrates β-glucan and avicel, respectively. The enzyme is highly stable in neutral and alkaline pH and showed a half-life of 11.29h, and 8.31h in pH 7.0 and 9.0, respectively. The enzyme is also compatible with commercial detergents (Tide, Surf, Ghadi, Raj, and Healing tree) of the Indian market and retained >85% enzyme activity. Concisely, robustness, extreme functionality, and detergent compatibility endorse EGaseBL as a potential bioresource for the detergent industry, in addition to its implications for the bioethanol industry.